Utilizing Prisoner Assimilation in the Midst of the Covid-19 Pandemic - Akbar, Andi Armansyah (Damhil Law Journal, 2024)
The purpose of this study is to find out more about how to utilize the assimilation of prisoners in the midst of the Covid-19 pandemic.Â  The research method used is normative legal research using a statutory approach. The results of the research in this study are that the assimilation of prisoners in the midst of the Covid-19 pandemic is a step by the government in this case the Minister of Law and Human Rights in an effort to prevent the spread of the covid-19 virus in prisons en masse. In addition, it provides utility for prisoners and the government in terms of comfort and security in LAPAS due to the reduction in occupant capacity from 99% overcapacity to 79% so that there are also budget savings from the state in terms of care and health more specifically food ingredients for prisoners.